Departure time choice behavior for hurricane evacuation planning: The case of the understudied medically fragile population. (May 2015) - Ng, ManWo; Diaz, Rafael; Behr, Joshua
Highlights: First study to examine the evacuation time choice of the special needs population. Key differences exist between the medically fragile and non-medically fragile. Different definitions of medically fragile are explored. Abstract: Despite the non-trivial number of (non-institutionalized) residents with special needs – referred to as the medically fragile population in this paper – there is virtually no research available to guide the hurricane evacuation planning for this population group. One area is their evacuation time choice behavior that can have tremendous implications for their safety as well as the logistics of the evacuation process. In this paper, we fundamentally advance our understanding of the evacuation timing behavior of this heavily understudied, and potentially vulnerable, population group. Analysis indicates that key differences exist between the medically fragile and non-medically fragile population.